Waiting for Solon: Audience Expectations in Herodotus - Branscome, David (Histos, 2015)
In this article, I focus not so much on what Solon actually says and does in his conversation with Croesus, but on what Herodotus’ readers, as well as Croesus himself, think Solon might say or do. I argue that Herodotus uses analogous episodes, those of Gyges, Candaules, and Candaules’ wife, of Arion and Periander, and of Bias/Pittacus and Croesus, to shape readers’ expectations of Solon’s conversation with Croesus, but he then subverts many of those expectations within the conversation itself. In so doing, Herodotus emphasises the programmatic function for the Histories of much of what Solon tells Croesus.